Study on the application of modified negative pressure wound therapy with instillation in cervical anastomotic leakage after oesophageal cancer surgery - Zhou, Linrong; Li, Cui; Guan, Xuehong; Xie, Jing; Lin, Wanli; Wu, Bomeng; Chen, Ying; Huang, Jiawei; Gong, Lanjuan (Frontiers in Oncology, 2025)
AimsThis study aims to explore the feasibility and safety of modified negative-pressure wound therapy with instillation (NPWTi) for the treatment of cervical anastomotic leakage (CAL) after oesophageal cancer surgery.MethodsA retrospective analysis was conducted on 17 patients who developed CAL after oesophageal cancer surgery and received modified NPWTi treatment at our hospital from 2021 to 2024. The primary outcome was the time to healing, defined as the number of days from the initiation of modified NPWTi to complete fistula closure. Secondary outcomes included wound odour improvement and patient comfort.ResultsA total of 17 patient were collected, including 10 men and seven women, with an average age of 73.71 ± 8.01 years. None received neoadjuvant therapy, and no patients had diabetes; preoperative albumin was 38.77 ± 3.58 g/L. The occurrence of CAL was noted at 8.88 ± 3.15 d (95% CI: 7.26 to 10.51 d) post-surgery. The modified treatment was commenced 0–12 d after CAL diagnosis, with the earliest case starting on the day of diagnosis. The mean duration of modified NPWTi was 10.88 ± 6.54 d (95% CI: 7.52 to 14.25 d). For the primary outcome, the time from treatment initiation to complete healing was 15.00 ± 7.26 d (95% CI: 11.27 to 18.73 d), with a minimum of five days. No mediastinal or pleural infections related to NPWTi occurred during the treatment. For the secondary outcomes, a significant improvement in wound odour was observed following the administration of the modified NPWTi (P<0.001), with an improvement rate of 100% (95% CI: 85-100%). During the treatment, the patients reported feeling comfortable and expressed overall satisfaction.ConclusionModified NPWTi demonstrated significant efficacy and convenience in treating CAL after oesophageal cancer surgery, benefiting both patients and healthcare providers with good safety profiles, thus warranting broader clinical application.